Evaluation of the radiofrequency performance of a wide-bore 1.5 T positron emission tomography/magnetic resonance imaging body coil for radiotherapy planning. (January 2021) - Branderhorst, Woutjan; Steensma, Bart R.; Beijst, Casper; Huijing, Erik R.; Alborahal, Cezar; Versteeg, Edwin; Weissler, Bjoern; Schug, David; Gebhardt, Pierre; Gross-Weege, Nicolas; Mueller, Florian; Krueger, Karl; et al.
Abstract: Background and purpose: The restricted bore diameter of current simultaneous positron emission tomography/magnetic resonance imaging (PET/MRI) systems can be an impediment to achieving similar patient positioning during PET/MRI planning and radiotherapy. Our goal was to evaluate the B1 transmit (B1 + ) uniformity, B1 + efficiency, and specific absorption rate (SAR) of a novel radiofrequency (RF) body coil design, in which RF shielded PET detectors were integrated with the specific aim of enabling a wide-bore PET/MRI system. Materials and methods: We designed and constructed a wide-bore PET/MRI RF body coil to be integrated with a clinical MRI system. To increase its inner bore diameter, the PET detectors were positioned between the conductors and the RF shield of the RF body coil. Simulations and experiments with phantoms and human volunteers were performed to compare the B1 + uniformity, B1 + efficiency, and SAR between our design and the clinical body coil. Results: In the simulations, our design achieved nearly the same B1 + field uniformity as the clinical body coil and an almost identical SAR distribution. The uniformity findings were confirmed by the physical experiments. The B1 + efficiency was 38% lower compared to the clinical body coil. Conclusions: To achieve wide-bore PET/MRI, it is possible to integrate shielding for PET detectors between the body coil conductors and the RF shield without compromising MRI performance. Reduced B1 + efficiency may be compensated by adding a second RF amplifier. This finding may facilitate the application of simultaneous whole-body PET/MRI in radiotherapy planning.